Management innovation strategy for sustainable coffee agroforestry development in Medono Village, Purworejo Regency - Isna Windani; Dyah Panuntun Utami; Istiko Agus Wicaksono; Uswatun Hasanah (University of Islam Malang, 2026)
espite growing interest in coffee-based agroforestry as a strategy for rural development, few studies have comprehensively examined socio-cultural conditions, community and stakeholder perceptions, and strategic factors supporting sustainable coffee agroforestry development within an integrated framework. This study aims to examine the socio-cultural profile supporting coffee agroforestry development in Medono Village, analyze community and stakeholder perceptions regarding its development, and formulate management innovation strategies for sustainable coffee agroforestry development. The novelty of this study lies in integrating socio-cultural analysis, stakeholder perception assessment, Importance–Performance Analysis (IPA), and SWOT analysis to formulate context-specific management innovation strategies for sustainable coffee agroforestry development at the village level. The research employed descriptive, qualitative, and quantitative approaches. Data were collected through questionnaires, observations, and in-depth interviews involving 72 respondents. The findings reveal that Medono Village possesses strong social cohesion, which serves as valuable social capital for coffee agroforestry development. The local economy is predominantly based on agricultural activities, while diverse natural resources, including plantations, forests, and mountainous landscapes, support the area. Community and stakeholder perceptions toward coffee agroforestry development were highly positive, with average scores indicating strong support for its development. The IPA results identified several improvement areas, particularly agroforestry support facilities and facility cleanliness, although no attribute was located in the main priority quadrant. SWOT analysis indicates that Medono Village has substantial strategic potential for sustainable coffee agroforestry development through integrated management strategies that optimize local resources, strengthen institutional collaboration, improve supporting facilities, and promote ecological and economic sustainability.